The perfect finance minister: Whom to appoint as finance minister to balance the budget? - Beate R. Jochimsen; Sebastian Thomasius (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The role and influence of the finance minister within the cabinet are discussed with increasing prominence in the recent theoretical literature on the political economy of budget deficits. It is generally assumed that the spending ministers can raise their reputation purely with new or more extensive expenditure programs, whereas solely the finance minister is interested to balance the budget. Using a dynamic panel model to study the development of public deficits in the German states between 1960 and 2009, we identify several personal characteristics of the finance ministers that significantly influence budgetary performance. Namely her professional background seems to affect budget deficits. During times of fiscal stress, our results can guide prime ministers in the nominating of finance ministers in order to assure sound budgeting.
Keywords: D78; H30; H74; 330; Fiscal policy; public deficit; political economy; finance minister